(untitled) (Research, Society and Development, 2021)
The interception of malocclusions in early stages reduces the severity of the present problem, contributing to a balanced growth of bone bases. Among the malocclusions that must be corrected in advance, we highlight cross bites and open bites in that order of priority. A range of therapeutic possibilities are described in the literature, including the use of a removable appliance with expander and lingual grid. However, little evidence validates this form of treatment based on this assumption. The objective of the present study was to evaluate the effectiveness of the removable appliance with expander and lingual grid to correct posterior crossbite associated with anterior open bite. Orthodontic documentation of 148 children aged 5 to 12 years who received treatment between 2009 and 2018 was analyzed. The effectiveness or not of the treatment was verified by analyzing photographs and study models in two stages of treatment: initial and final. After performing Shapiro-Wilk tests, the frequencies were compared using the chi-square test and the variables were calculated using the Kruskal-Wallis test. It was found that 74% of cases of crossbite and 91.7% of cases of open bite were corrected. Thus, it can be concluded that the correction of open bite and crossbite was achieved with the use of these devices.